New York Café - Dean, Michael, 1949-; Illustrated by Richardson, Peter (Oxford, New York Oxford University Press, 2008)
Word count 1,600 CD: American English Suitable for young learners Bestseller
Include Color Illustration
Keywords: Readers (Adult) -- Computer crimes -- Reading comprehension